Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fninf.2021.578369
|View full text |Cite
|
Sign up to set email alerts
|

X-Vectors: New Quantitative Biomarkers for Early Parkinson's Disease Detection From Speech

Abstract: Many articles have used voice analysis to detect Parkinson's disease (PD), but few have focused on the early stages of the disease and the gender effect. In this article, we have adapted the latest speaker recognition system, called x-vectors, in order to detect PD at an early stage using voice analysis. X-vectors are embeddings extracted from Deep Neural Networks (DNNs), which provide robust speaker representations and improve speaker recognition when large amounts of training data are used. Our goal was to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 70 publications
1
16
0
2
Order By: Relevance
“…This study, like others, also found differences by sex including in speech, and shows the value of connected speech tasks. 25,26 More research is needed, including longitudinal analysis from this study, to determine which measures are most sensitive to change over time.…”
Section: Discussionmentioning
confidence: 99%
“…This study, like others, also found differences by sex including in speech, and shows the value of connected speech tasks. 25,26 More research is needed, including longitudinal analysis from this study, to determine which measures are most sensitive to change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that it is also possible to automatically discriminate PD from healthy controls at an early stage via handcrafted features extracted from speech ( 16 ). Moreover, in ( 17 ) a new DM technique (named X-vectors) was presented, which employs modern machine learning (ML) methods rather than designing handcrafted features. Improved classification results with X-vectors were obtained, validating the approach for early PD detection, using both high-quality speech recordings performed in laboratory settings and speech data acquired through telephone recordings.…”
Section: Current State Of Digital Biomarkers In Parkinson's Diseasementioning
confidence: 99%
“…First, we performed classifications from a subset of the high-level speech features, using support vector machines (SVM). Then we merged the SVM classifier (detailed in Supplementary material) with two classifiers [19,20], based on short-term features (calculated at the frame level), which characterize the spectral envelope and capture the articulatory disruptions. The fusion consisted on a majority vote of the three classes predictions, using the classifiers equal error rate thresholds as decision threshold.…”
Section: Classificationmentioning
confidence: 99%